0
$\begingroup$

The Problem: Suppose that $X_1,\dots,X_n$ are independent random variables with the same absolutely continuous distribution. Let $f$ denote their common marginal PDF. Set $Y=\min(X_1,\dots,X_n)$ and $Z=\max(X_1,\dots,X_n)$. Show that $Y$ and $Z$ are both absolutely continuous, and find their marginal PDFs.

My Thoughts: We begin by finding the CDF of $Y$. For $t\in\mathbb R$ we have \begin{equation}\begin{split} F_Y(t)&=P(Y\leq t)=P(\min(X_1,\dots,X_n)\leq t)=1-P(X_1>t,\dots,X_n>t)\\ &=1-P(X_1>t)\cdots P(X_n>t)\\ &=1-[1-F(t)]^n, \end{split}\end{equation} where in the fourth step we used the independence of the random variables $X_1,\dots,X_n$, and in the last step we used the fact the latter random variables have the same distribution which we call $F$. By the absolute continuity of the random variables $X_1,\dots,X_n$, we may use the chain rule to differentiate the expression for $F_Y$ to obtain $$f_Y(t)=nf(t)[1-F(t)]^{n-1}=nf(t)\left[1-\int_{-\infty}^tf(s)\,ds\right]^{n-1}.$$ It follows that $Y$ is an absolutely continuous random variable.
Next, we find the CDF of $Z$. For $t\in\mathbb R$ we have \begin{equation*}\begin{split} F_Z(t)&=P(Z\leq t)=P(\max(X_1,\dots,X_n)\leq t)=P(X_1\leq t,\dots,X_n\leq t)\\ &=P(X_1\leq t)\cdots P(X_n\leq t)\\ &=F(t)^n, \end{split}\end{equation*} where in th fourth step we used the independence of the random variables $X_1,\dots,X_n$. Since the latter mentioned random variables are absolutely continuous, we may use the chain rule to differentiate the expression for $F_Z$ to obtain $$f_Z(t)=nF(t)^{n-1}f(t)=nf(t)\left[\int_{-\infty}^tf(s)\,ds\right]^{n-1}.$$ It follows that $Z$ is an absolutely continuous random variable.


Could anyone please provide feedback on the correctness of my proof above?

Thank your for your time, it is much appreciated.

$\endgroup$
3
$\begingroup$

The derivative $F_X'$ of the distribution function of a random variable $X$, if it exists, is always measurable and non-negative, but its integral need not be $1$. So just proving that the derivative exists is not enough. In both cases you can see that the derivative you obtained actually integrates to $1$ and the formula $F_X(x)=\int_{-\infty} ^{x} F_X'(t)dt$ holds. Hint for computing the integral: putting $h(t)=\int_{-\infty}^{t} f(s)ds$ helps in both cases.

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.